CLINIC-LABORATORY AND ENDOSCOP FEATURES OF MOTION OF UNSPECIFIC ULCEROUS COLITIS - Вірстюк, Н. Г.; Лучко, О. Р.; Лосюк, Л. В.; Хасанов, О. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Complex clinical and laboratory-instrumental research is conducted 30 patients with an unspecific ulcerous colitis (NVC). It is exposed, that the about half of patients (53,3%) on NVC have overintestinal displays, and in 43,8% cases overintestinal defeat the two and more of organs and systems. Among of overintestinal displays NVC the defeats of liver (56,3%) which varied from reactive hepatitis (44,4%) to the autoimmune defeats of liver, were most widespread, in particular autoimmune hepatitis (33,3%) and initial sclera holangite (22,3%). It is set that at patients on NVC with autoimmune defeat of liver, spondiloartrite and psoriasis a clinical picture did not answer endoscope therefore by us the group of overintestinal defeats which insignificantly depend on activity of inflammatory process of mucus shell in a colon is selected. For other group characteristic was appearance of displays in the moment of high activity NVC and reduction or disappearance in the stage of remiss of disease – reactive arthritis, reactive hepatitis, defeat of skin as key erythematic, defeat of mucus shell of cavity of mouth and eyes.